MOTIVATION IN EDUCATION ACCORDING TO THE PHILOSOPHY OF MAX HORKHEIMER AND THEODOR ADORNO: UKRAINIAN RECONCEPTUALIZATION - Fialko, Nataliia (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
This study is an attempt to reconstruct the concept of motivation, which was developed for the field of education by the founders of the Frankfurt School of Social Research, Theodor Adorno and Max Horkheimer. The emphasis is on such key theses as the democratization of education and overcoming totalitarian education, the role of the individual in education and autonomy in decision-making, spiritual development and emancipation of the individual against the instrumentalization of man with an emphasis on professional education, the ideological role of philosophy in education and the criticism of ideologies. It is demonstrated that the ideas of critical social theory, which were consciously applied by Adorno and Horkheimer to reform education, have a certain potential, but also certain limits for the development of proper motivation of the individual for his conscientious inclusion in education. Critical social theory explores the topic of legitimation of education too abstractly, reducing it to the individual’s need for freedom and spiritual development, and avoiding a detailed institutional analysis of the problems of educational development. The reconceptualization of the topic of motivation in education based on the ideas of Adorno’s and Horkheimer’s critical social theory, carried out by Ukrainian philosophers, develops the theory of education in the direction of the philosophy of generations, institutional legitimation of education as the basis of proper personal motivation in education. The contribution of Mariia Kultaieva, Vitalii Bryzhnik and Mykhailo Boichenko to the criticism and development of the ideas of critical social theory is analyzed, in particular to its assessment as a reflection on reflection in education. Critical understanding of the past (as a reflection on the past) also requires a reflexive assessment of its significance in order to determine priorities for education, which prepares the person to change the future of society for the better.